God's Fullness in Bodily Form: Christ and Church in Colossians - Henderson, Suzanne Watts (The expository times, 2007)
This study explores the language of 'fullness' found in Colossians 2:9-10, where the Pauline writer suggests that Christ's fullness now manifests itself in those who are 'in him'. As Christ's body, the church has been filled with the power of God and presses toward the full expression of God's renewal of 'all things'.